Effects of Varieties, Cutting Health and Fungicide Application on Chrysanthemum White Rust - Evi Silvia Yusuf; Kurniawan Budiarto; I. Djatnika; Suhardi Suhardi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2017)
White rust caused by fungal pathogen Puccinia horiana P. Henn. is one devastated disease that could make significant economic loss in chrysanthemum production. The study of effects of varieties, cutting health and fungicide application on chrysanthemum white rust was established. The treatments were arranged in split-split plot completely randomized design with three replications. Three chrysanthemum varieties i.e. cv. Puma White, Reagent Purple and Town Talk served as main plot. Seedlings with 20 % intensity of white rust infection and symptomless functioned as sub plot, while fungicide application on the transplanted cutting (no fungicide) and dithiocarbamate (AntracolR 75 WP, 2 g L-1) application served as sub-sub plot. Result showed genetic background of the cultivars significantly determined the degree of infection of white rust. Reagent Purple exhibited least disease intensities. Fungicide application was less effective in controlling white rust development, yet gave significant impact on the plant height and number of leaves of chrysanthemum plants. Cuttings selection based on the visual observation on the presence or absence of white rust pustules symptom did not gave significant differences on the further development of the disease. The symptomless cuttings were also infected with this fungal disease after the cuttings were planted under plastic house.